2022
DOI: 10.3390/cancers14143464
|View full text |Cite
|
Sign up to set email alerts
|

Brain Gliomas and Ollier Disease: Molecular Findings as Predictive Risk Factors?

Abstract: Background: Ollier disease (OD) is a rare nonhereditary type of dyschondroplasia characterized by multiple enchondromas, with typical onset in the first decade of life. Surgery is the only curative treatment for primary disease and its complications. Patients with OD are at risk of malignant transformation of enchondromas and of occurrence of other neoplasms. Methods: A wide literature review disclosed thirty cases of glioma associated with OD, most of them belonging to the pre-molecular era. Our own case was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The biomolecular studies performed in some reported cases of Ollier disease with brain glioma have shown a positive IDH1 mutation in a majority of cases. Corvino S et al described 31 reported cases of Ollier disease with brain glioma, and biomolecular studies were performed only in 10 patients, where 8 patients showed positive IDH1-mutation [ 9 ]. Prokopchuk et al described the non-skeletal neoplasms worldwide and found only 5 cases of astrocytoma associated with Maffucci syndrome [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomolecular studies performed in some reported cases of Ollier disease with brain glioma have shown a positive IDH1 mutation in a majority of cases. Corvino S et al described 31 reported cases of Ollier disease with brain glioma, and biomolecular studies were performed only in 10 patients, where 8 patients showed positive IDH1-mutation [ 9 ]. Prokopchuk et al described the non-skeletal neoplasms worldwide and found only 5 cases of astrocytoma associated with Maffucci syndrome [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corvino et al reported that the medical literature contains over thirty documented cases of glioma associated with Ollier disease, whereas the number of reported cases of astrocytoma in combination with Maffucci syndrome is significantly fewer, and the majority of those cases were described before the era of molecular genetics [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with somatic point variants in IDH1 (OMIM*147700) including c.394C>A p.(R132S) and c.395G>A p.(R132H) (Vissers et al, 2011). However, the underlying variants in many patients have not been identified (Corvino et al, 2022). Here, we present a 22‐year journey to provide a molecular diagnosis for a patient with MC‐HGA and offer recommendations for molecular diagnosis based on our experience.…”
Section: Figurementioning
confidence: 99%
“…However, the underlying variants in many patients have not been identified (Corvino et al, 2022). Here, we present a 22-year journey to provide a molecular diagnosis for a patient with MC-HGA and offer recommendations for molecular diagnosis based on our experience.…”
mentioning
confidence: 99%
“…A síndrome de Ollier é uma doença com a característica de ocorrência de múltiplos encondromas, que nada mais são do que tumores benignos de cartilagem, com característica não hereditária, de aparecimento geralmente na primeira década de vida e de prevalência de 1:100.000, sendo assim considerada rara. A alteração na ossificação encondral por mutações de genes e consequentes problemas em vias de sinalização estão associadas à principal suspeita de causa dessa síndrome (CORVINO, 2022).…”
Section: Introductionunclassified